1993
DOI: 10.1161/01.atv.13.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin overexpression is associated with arterial smooth muscle cell proliferation in vitro.

Abstract: To isolate the genes involved in the cell cycle G1 phase progression of arterial smooth muscle cells (SMCs), a cDNA clone (M11) was previously selected by differential hybridization screening of a mid-G1 serum-stimulated SMC cDNA library. The delay of induction after mitogenic stimulation, time of expression, and need for new protein synthesis for full expression made it possible to classify this gene in the "delayed early" gene group. Determination of the partial M11 cDNA sequence showed full homology with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
82
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 31 publications
7
82
0
1
Order By: Relevance
“…6C). A closer interpretation of the RT-qPCR data revealed a high basal expression of OPN in the presence of the DMSO vehicle, which has been observed previously in smooth muscle cells (15). Inhibition of p38 resulted in a trend toward reducing the level of ANG II induction of mRNA for all gene targets.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…6C). A closer interpretation of the RT-qPCR data revealed a high basal expression of OPN in the presence of the DMSO vehicle, which has been observed previously in smooth muscle cells (15). Inhibition of p38 resulted in a trend toward reducing the level of ANG II induction of mRNA for all gene targets.…”
Section: Resultssupporting
confidence: 81%
“…The confirmed extent of induction of OPN mRNA levels in response to hypertensive disease was particularly intriguing due to the previous implications that OPN regulates VSMC proliferation and migration and is overexpressed during postangioplasty restenosis (15,35,50). In addition, OPN is a matricellular gene that is known to be transcriptionally regulated by ANG II and ERK signaling (7).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…In vitro, more than a dozen factors in plasma, platelets, endothelial cells, SMCs, and macrophages can each stimulate the proliferation of SMCs (Willerson et al 1991, Ross 1993, Casscells 1991a, and new factors are reported every few months (Gressens et al 1993, Gadeau et al 1993, Grove et al 1993, Shing et al 1993. In many cases, these factors also upregulate other growth factors and their receptors (Hu et al 1992, Nicholson and Hajjar 1992, Hajjar and Pomerantz 1992, Schollmann et al 1992, Stiko-Rahm et al 1992, Itoh et al 1993.…”
mentioning
confidence: 99%